Kallimni'Arabi Aktar = (3cdefj YQHj CcJQ (B: an upper intermediate course in Spoken Egyptian Arabic 3 /s - Louis, Samia; Guirges, Nessim; International AUC-Oxford University Conference on Languageand Linguistics 2006 : Cairo, Egypt) (Cairo, New York : The American University in Cairo Press, 2008)
This book is the third of a series of collected volumes on language and linguistics published by the AUC Press. The chapters are based on papers delivered at the second International AUC-Oxford University Conference on Languageand Linguistics, held in 2006 at the American University in Cairo. The contributions reflect global concerns related to both the Arabic and the English languages and to linguistics in general and are the work of world-renowned scholars, whose concerns address diverse but related topics in language and information dissemination. The resulting collection presented here boasts a wide range of scholarship from the Arabic-speaking world as well as the United States, Canada, and western and easternEurope.''Twelve chapters grouped in four sections cover awide variety of topics - phonetics, syntax, variation, computational linguistics, and globalization and its effects on linguistic discourse and language teaching - and reflect the latest research in the various fields, together giving a global perspective on Arabic linguistics.'--BOOK JACKET
Chapters... are based on papers delivered at the second International AUC-Oxford University Conference on Languageand Linguistics, held in 2006 at the American University in Cairo'--Jacket flap
Book is accompanied by one CD, entitled 2Kallimni'Arabi Aktar3 bearing the same call number and available at Koleksi Media
Keywords: Arabic language -- Dialects -- Egypt -- Textbooks for foreign speakers -- English; Arabic language -- Egypt -- Self-instruction.; Arabic language -- Spoken Arabic -- Textbooks for foreign speakers -- English